Re-generate resilience to deal with climate change: A data-driven pathway for a liveable, efficient and safe city - Palermo, Annunziata; Chieffallo, Lucia; Virgilio, Sara (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Cities are vulnerable to the effects of the climate. Building resilience to contain the risks for inhabitants, businesses and infrastructures deriving from the impact of climate change represents a challenge for local planners and public decision-makers. To win it, it is necessary to include the most suitable adaptation actions to contain the conditions of vulnerability in the local urban regeneration processes. To this end, the authors have increased and applied a methodology for defining and mapping climatic vulnerability, with a particular focus on the built environment. The main element of integration and updating concerns the use of Copernicus satellite remote sensing data. The application to the case study demonstrates the adequacy of such data for the research needs and the relative utility in terms of spatial resolution of the results. The vulnerability map into a more accurate definition scale helps the planner to integrate the common regeneration goals with more specific climatic resilience goals. In fact, basing on the results obtained for the case study, the authors define adaptive design solutions aimed at regenerating local resilience in terms of liveability, efficiency and safety.